Detecting Platform Development for Guangzhou URT Door Control Unit Based on PLC - CHEN Xijun (机车电传动)
The development of a detecting platform for common door control unit adopted in Guangzhou metro was introduced. The platform was established based on Siemens S7-200 series PLC, and the WinCC was used to design the upper computer software. This platform provided detection and malfunction indications, and could detect the fault of door control unit accurately, which improved the efficiency of inspection and maintenance.